2021
DOI: 10.3390/nu13062039
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Dietary Change since the Outbreak of COVID-19 in Japan

Abstract: In Japan, dietary habits have greatly changed since the coronavirus disease (COVID-19) outbreak; we examined factors related to dietary changes. An online cross-sectional questionnaire survey was conducted in November 2020 among 6,000 Japanese adults (aged 20–64 years) registered with a research company and gathered data on demographics, socioeconomic factors, medical history, COVID-19 status of the respondent’s family and neighbors, fear of COVID-19, and changes in lifestyle and dietary habits since the COVID… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 29 publications
4
29
0
2
Order By: Relevance
“…Balanced dietary habits are the most common health behavior. Simpo et al [16], in their study on changes in lifestyle and dietary habits during the novel COVID-19 infection epidemic in Japanese adults aged 20-64 years, found that healthy dietary habits were associated with anxiety about COVID-19, changes in exercise and sleep time, and smoking, which approximated the findings of the present study. Low nutrition in old age is a significant cause of frailty and sarcopenia, and older adults need to pay more attention to their dietary habits than younger people to maintain a healthy life.…”
Section: Discussionsupporting
confidence: 84%
“…Balanced dietary habits are the most common health behavior. Simpo et al [16], in their study on changes in lifestyle and dietary habits during the novel COVID-19 infection epidemic in Japanese adults aged 20-64 years, found that healthy dietary habits were associated with anxiety about COVID-19, changes in exercise and sleep time, and smoking, which approximated the findings of the present study. Low nutrition in old age is a significant cause of frailty and sarcopenia, and older adults need to pay more attention to their dietary habits than younger people to maintain a healthy life.…”
Section: Discussionsupporting
confidence: 84%
“…Results of multivariate analyses: Predictors of MAFLD developmentas other lifestyle habits, would differ by age 11,12. As expected, our results were consistent with those of Alpers et al27 One possible rea-…”
supporting
confidence: 92%
“…22 Additionally, recent evidence revealed that lifestyle changes post-COVID-19 were associated not only with obesity 3,4 and obesity-related diseases (NAFLD 23 ) but also with less healthy dietary habits. 12 In this study, we confirmed routine late-night meals as a predictor of MAFLD development using multivariate analysis of interaction effects (Table S3). These results suggested that consuming late-…”
Section: Role Of Dietary Habits In Mafld Development Before and Durin...supporting
confidence: 71%
“…Plenty of research has been conducted since the COVID-19 pandemic began, particularly on dietary and eating habit changes. Based on an online cross-sectional questionnaire survey conducted at one time point in November 2020 when the Japanese government issued stay-at-home requests, only 8.2% adults out of the 6000 respondents experienced an unhealthier change from their initial dietary habits as they live alone with higher stress levels from the lack of social support, while 71.6% reported unchanged diets [ 74 ]. The unchanged dietary habit was also noted from 34 provinces across China with 71.4% of the participants noting no changes in their appetite [ 75 ].…”
Section: Resultsmentioning
confidence: 99%